Instructional Concept Map Techniques in the Planning Stage– Project Based Learning on Student Argumentation Skills - Rizki Putri Puspitasari; Sri Widoretno; Bowo Sugiharto; Sri Dwiastuti; Chandra Adi Prabowo (JURNAL BIOEDUKATIKA, 2022)
Argumentation skill is one of the characteristics of HOTS (Higher Order Thinking Skill) that students need in learning. This study aims to identify the effect of applying the concept map instructional technique at the planning an investigation stage of PjBL on students’ argumentation skills. The study used a quasi-experimental research design with a posttest-only nonequivalent group design. The subject of the study is the tenth grade students of Senior High School (SHS). There were 72 students. The research instrument uses 11 numbered argumentative questions in the form of multiple-choice true-false reasoned questions that match the argumentation component. Data analysis used quantitative analysis based on posttest scores. The results showed that the significance value of the t-test on the argumentation skill score was 0.000, meaning that the significance value was <0.05, so it can be stated that there was an effect of applying the concept map instructional technique in the planning and investigation stage in the PjBL model on students’ argumentation skills.